Reflections on work in the contemporary context of the creative economy - Haubrich, Gislene Feiten; Bessi, Vânia Gisele; Bohnenberger, Maria Cristina; Freitas, Ernani Cesar de (Organizações & Sociedade, 2020)
This article aims to reflect upon the concept of work in the field of creative economy, as well as its contribution to the understanding of the culture of these kinds of organizations in the contemporary context. It is an exploratory study, based on bibliographic and documentary research. The theoretical framework is grounded on the notions of work, with emphasis on immaterial work (Lazzarato & Negri, 2001; Schwartz & Durrive, 2015), rhizome (Deleuze & Guattari, 2000) and symbolic power (Bourdieu, 2002) to reflect on the context of creative economy (Florida, 2011; Howkins, 2013). As a main result of this initial reflection, it is understood that the interactions that are expected for and by creative economy workers move between a rhizomatic and libertarian perspective and a structural one based on shared values. In this case, organizations assume a different configuration through the culture expressed by norms and symbolic disputes, incorporated by each group in the conduct of their projects.